Computational fluid dynamics simulation and full-scale experimental model inter-comparison of the wind flow around a university campus. Issue 1 (February 2017) - Dhunny, AZ; Toja-Silva, F; Peralta, C; Lollchund, MR; Rughooputh, SDDV
In this article, results obtained from two computational fluid dynamics solvers, WindSim and OpenFOAM, have been compared for the wind flow around the University of Mauritius' campus for different wind directions, and a reference incident wind speed at diverse height above ground level. A grid resolution study is performed for both software and the mean differences of the two solvers with multiple turbulence models (standard k-ε, k-ε with Yap correction, and renormalization group k-ε) are analyzed with onsite measured data. The article concludes that the best results for the computational fluid dynamics simulation of the wind flow around buildings are obtained using OpenFOAM with k-ε turbulence model including Yap correction.